THEORETICAL PRINCIPLES OF ORGANIZING COOPERATION BETWEEN THE NATIONAL GUARD OF UKRAINE AND SECURITY SECTOR INSTITUTIONS IN ENSURING PUBLIC SECURITY - Danko, Vitalii (Honor and Law, 2025)
The article analyzes theoretical, legal, empirical, and comparative aspects of the organization of interaction between the National Guard of Ukraine and components of the security sector in the field of public safety. It examines the legal status, mandate, and evolution of the role of the National Guard of Ukraine, in particular its dualistic nature as a military formation with law enforcement functions, as well as related constitutional debates. The theoretical foundations, principles, forms, and levels of interagency cooperation are identified. Based on empirical data and analytical reports, the current state of coordination is assessed, and challenges and gaps in legislative and practical implementation are identified. Comprehensive recommendations are formulated for optimizing the legislative, operational, and strategic aspects of cooperation in order to improve the effectiveness of Ukraine's public safety system.